Promising therapeutic efficacy of a novel reduced expression in immortalized cells/dickkopf‐3 expressing adenoviral vector for hepatocellular carcinoma. Issue 10 (26th September 2017) - Sawahara, Hiroaki; Shiraha, Hidenori; Uchida, Daisuke; Kato, Hironari; Kato, Ryo; Oyama, Atsushi; Nagahara, Teruya; Iwamuro, Masaya; Horiguchi, Shigeru; Tsutsumi, Koichiro; Mandai, Mari; Mimura, Tetsushige; et al.
Abstract: Background and Aim: Reduced expression in immortalized cells (REIC)/dickkopf‐3 (Dkk‐3) is a tumor suppressor gene that is downregulated in various cancers. In our previous study of prostate cancer, the REIC/Dkk‐3‐expressing adenoviral vector (Ad‐REIC) was found to induce cancer‐selective apoptosis. This study recently developed a novel super gene expression (SGE) system and used this system to re‐construct an Ad‐REIC vector, termed the Ad‐SGE‐REIC, to achieve more effective therapeutic outcomes. In this study, the therapeutic effects of Ad‐SGE‐REIC on hepatocellular carcinoma (HCC) was assessed. Methods: Human HCC cell lines (HLE, Huh7, HepG2, HLF, SK‐Hep1, and PLC), human HCC tissues, and mouse HCC cell line (Hepa1‐6) were used in this study. REIC/Dkk‐3 expression was assessed by immunoblotting and immunohistochemistry. The relative cell viability and the apoptotic effect were examined in vitro, and the anti‐tumor effects of Ad‐SGE‐REIC treatment were analyzed in the mouse xenograft model. This study additionally assessed anti‐tumor immunological effects on the immunocompetent mice. Results: REIC/Dkk‐3 expression was decreased in HCC cell lines and HCC tissues. Ad‐SGE‐REIC reduced cell viability and induced apoptosis in HCC cell lines (HLE and Huh7), inhibited tumor growth in the mouse xenograft model, and demonstrated in vivo anti‐cancer immunostimulatory effects on the HCC cell line (Hepa1‐6). Conclusions: Ad‐SGE‐REIC treatment not only enhanced cell killing effects in vitro but also elicited significant therapeutic effects, with tumor growth suppression, in vivo . REIC/Dkk‐3 gene therapy using Ad‐SGE‐REIC potentially represents an innovative new therapeutic tool for HCC.